Evaluation of Industrial Field Practice Program using the Tyler Model in the Informatics Engineering Education Department - Yuliawati Yunus; Ambiyar Ambiyar; Fahmi Rizal (Jurnal Paedagogy, 2024)
This research aims to describe the evaluation implementation of industrial field practices in the informatics engineering education study program, Faculty of Teacher Training and Education, Universitas Putra Indonesia "YPTK" Padang. This research used an evaluation method with the Tyler Evaluation Model (Goal Oriented Model). Based on this method, data was collected through the following steps: 1). Identify the objectives of industrial field practice; 2) formulate indicators for the achievement goals that have been set; 3) formulate the data obtained with indicators. The main objective is divided into sub-component objectives, namely: sub-component of program objectives, sub-component of attitudes, and sub-component of achieving program objectives. All indicators included in the sub-components were analyzed using the mixed method technique (quantitative and qualitative) and obtained an average score of 84.4 %. It means that the implementation of industrial field practice in the informatics engineering education study program, Faculty of Teacher Training and Education, Universitas Putra Indonesia "YPTK" Padang, is in a good category. The impact of the implementation of industrial field practices can run smoothly in accordance with the program objectives.